Antimicrobial Photodynamic Therapy (aPDT) as a Disinfection and Biomodulation Approach in Implant Dentistry - de Souza Rastelli, Alessandra Nara [UNESP] (Wiley, 2021)
This article is a highlight of the paper by Choe et al. in this issue of Photochemistry and Photobiology. In that review paper, the disinfection and biomodulation outcomes promoted by antimicrobial photodynamic therapy (aPDT) on peri-implantitis infection were stated and discussed. The killing of the oral pathogens by aPDT is based on the generation of reactive oxygen species (ROS). Besides that, biomodulation can also be provided by aPDT and improve the healing and modulate the inflammatory process. Although aPDT has shown positive effects on the treatment of peri-implantitis disease mainly as a complimentary technique, the authors suggested that more and standardize clinical studies are needed to support the clinical application of aPDT for that purpose. Also, the standardization of parameters related to the light source and photosensitizers is required. In addition, nano-based materials may improve aPDT performance against oral biofilms and could increase the hopes of overcoming dental implant failures.